Spo2 Analysis on Development of IoT-Based Lung Function and Spo2 Measuring Device - Shavira, Nadya; Ariswati, Her Gumiwang; Hamzah, Torib (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2024)
Pulmonary dysfunction is a widespread issue, particularly in developing nations. It encompasses restrictive, obstructive, and mixed pulmonary function disorders that lead to a decrease in vital lung capacity, an increase in functional residual capacity, and a decline in blood oxygen concentration and saturation. This study aims to combine oximetry and spirometry into a single device, using the Internet of Things (IoT) technology to display results via a smartphone app. The focus is on analyzing oxygen saturation, with normal levels ranging from 96% to 100% in adults, alongside a heart rate of 60-100 beats per minute. The MAX30102 sensor measures oxygen saturation, and the Arduino Pro Mini and D1 Mini ESP32 microcontrollers process data. The Android-based app, developed using Kodular platform, integrates a MySQL database and connects to the device module via Wi-Fi. Ten respondents underwent five measurements, revealing an average error of ±0.88% for oxygen saturation (SpO2) and ±2.82% for heart rate measurements. The average data loss rate during transmission was ±0.66% for SpO2 and ±0.89% for heart rate. These findings highlight existing errors in the module. The research aims to facilitate remote health monitoring for healthcare professionals, improving accessibility and healthcare provision